Analysis of the influence of Marketplace Features and E-Wom on the Satisfaction of Online Buyers Shopee Students of Dehasen University Bengkulu City - Adam Ardiansyah; Karona Cahya Susena; Yudi Irawan Abi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of marketplace features on the satisfaction of Shopee online buyers, the students at Dehasen University, Bengkulu City. The type of this research is quantitative. The data analysis method used is multiple linear regression and the sample data collection method uses convenience sampling with 100 samples. The results of the marketplace feature have a significantly negative effect on Shopee Online Buyers Satisfaction among the Students at Dehasen University, Bengkulu City. This is proven by the results of the t test showing that the t value shows -3.850 and a significant value of 0.00 < 0.05 means Ha is accepted and H0 is rejected. E-wom has a significant effect on Shopee Online Buyers Satisfaction of Dehasen University Students, Bengkulu City. This is proven by the results of the t test showing that the t value is greater than t table (8.680 > 1.984) with a significant value of 0.000 < 0.05, meaning that H0 is rejected and Ha is accepted. The Marketplace (X1), E-wom (X2) features, together have a significant effect on Shopee Online Buyers (Y) Satisfaction of Dehasen University Students, Bengkulu City, this is proven by the F test showing the value of Fcount > Ftable (38.281 > 3, 09) with a significant value of 0.000. Based on the results of the multiple linear regression test, there is a coefficient of determination (R2) of 0.441 or 44.1%. This explains that the large variation in the dependent (Satisfaction) and independent variables (Marketplace and E-WOM Features) is (100%-44.1% and the result is 55.9%) online buyers' satisfaction is influenced by other variables not analyzed in this research. Keywords: Marketplace features, E-wom, online buyers' satisfaction1) Student2) Supervisors